2014
DOI: 10.1002/jcp.24838
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane X Receptor as the “Sensor and Effector” in Regulating Epigenome

Abstract: The pregnane X receptor (PXR, NR1I2) is a ligand-activated nuclear receptor which plays an essential role in organism's metabolic detoxification system by sensing the presence of xenobiotics and triggering detoxification responses. In addition to its role in xenobiotic metabolism, PXR has pleiotropic functions in regulating immune/inflammatory responses, cell proliferation, bile acid/cholesterol metabolism, glucose and lipid metabolism, steroid/endocrine homeostasis, and bone metabolism. Recent research sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…PXR also plays important roles in many biologic events such as hepatic energy metabolism, immune/inflammatory responses, cell proliferation, bone homeostasis, and the pathogenesis of inflammatory bowel disease and tumor development (reviewed in Konno et al, 2008;Ihunnah et al, 2011;Zhuo et al, 2014;Rathod et al, 2014;Ma et al, 2015). A previous study demonstrated that PXR was sequestered in the cytoplasm through the formation of a complex with heat shock protein (Hsp) 90 (Squires et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…PXR also plays important roles in many biologic events such as hepatic energy metabolism, immune/inflammatory responses, cell proliferation, bone homeostasis, and the pathogenesis of inflammatory bowel disease and tumor development (reviewed in Konno et al, 2008;Ihunnah et al, 2011;Zhuo et al, 2014;Rathod et al, 2014;Ma et al, 2015). A previous study demonstrated that PXR was sequestered in the cytoplasm through the formation of a complex with heat shock protein (Hsp) 90 (Squires et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the CYP1 gene family (1A1, 1A2 and 1B1) is transcriptionally regulated by AhR while the CYP2 (2A6, 2B6 and 2C8/9) as well as CYP3 (3A4) families are regulated by the PXR and CAR [33]. AhR is a ligand-dependent transcription factor to mediate the biotransformation and carcinogenic/teratogenic effects of environmental toxins [33].…”
Section: Generation Of Ros and Oxidative Stressmentioning
confidence: 99%
“…The expression of the CYP1 gene family (1A1, 1A2 and 1B1) is transcriptionally regulated by AhR while the CYP2 (2A6, 2B6 and 2C8/9) as well as CYP3 (3A4) families are regulated by the PXR and CAR [33]. AhR is a ligand-dependent transcription factor to mediate the biotransformation and carcinogenic/teratogenic effects of environmental toxins [33]. In most conditions, AhR is retained in the cytosol and formed complexes with the chaperone proteins, heat-shock protein 90kDa (HSP90), aryl hydrocarbon receptor interacting protein (AIP), and p23 in the absence of a ligand.…”
Section: Generation Of Ros and Oxidative Stressmentioning
confidence: 99%
“…However, PXR activation also induces differentiation of osteoblasts and apoptosis of osteoclasts and certain leukemia cells (Austin et al, 2015; Hassen et al, 2014; Igarashi et al, 2007; Kameda et al, 1996; Tabb et al, 2003), suggesting that control of cell proliferation by PXR is likely tissue and cell-specific. A similar theme plays out in cancer cells, in which, PXR differentially regulates cell growth through multiple mechanisms in a variety of cancers, including liver, prostate, breast, ovarian, endometrial, cervical, and colon (Braeuning et al, 2014; Kakehashi et al, 2013; Koutsounas et al, 2013; Luisier et al, 2014; Ma et al, 2015; Niu et al, 2014; Pondugula and Mani, 2013; Qiao et al, 2013; Ross et al, 2010; Rouquie et al, 2014; Shizu et al, 2013; Tinwell et al, 2014). Additionally, PXR is involved in regulating metastasis of cancer cells (Gupta et al, 2008; Masuyama et al, 2007; Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 85%
“…These concepts are contextual, as PXR protein in solution might associate with both co-repressors and co-activators in the presence or absence of ligands, thus challenging the current paradigm (Navaratnarajah et al, 2012). Furthermore, several modifications, particularly post-translational, are not ligand dependent and can modify receptor function in vitro and in tissues (Biswas et al, 2009; Biswas et al, 2011; Ma et al, 2015; Pondugula et al, 2015b; Smutny et al, 2013; Staudinger et al, 2011). Nonetheless, agonists such as rifampicin, SR12813, and chemotherapeutic drugs such as paclitaxel (Kliewer et al, 1998; Lehmann et al, 1998; Pondugula et al, 2015a; Pondugula et al, 2015c) bind to PXR.…”
Section: Introductionmentioning
confidence: 99%